Written space in the Latin West, 200 BC to AD 300 - Sears, Gareth; Keegan, Peter; Laurence, Ray (Bloomsbury Academy, 2013)
Written space / Ray Laurence and Gareth Sears -- Writing in Roman public space / Mireille Corbier -- Reading epigraphic culture, writing funerary space in the Roman city / Peter Keegan -- Movement, rhythms, and the (re)production of written space / David Newsome -- Time in written spaces / Robert Hannah -- Graffiti's engagement. the political graffiti of the late roman republic / Tom Hillard -- Writing in public space from child to adult : the meaning of graffiti / Renata Senna Garraffoni and Ray Laurence -- Inscribed in the city: how did women enter "written space"? / Emily Hemelrijk -- Slaves and children in a Roman villa: writing and space in the villa San Marco at Stabiae / Eamonn Baldwin, Helen Moulden and Ray Laurence -- Text, space, and the urban community: a study of the platea as written space / Francesco Trifilò -- Writing up the baths : reading monumental inscriptions in Roman baths / Alison Cooley -- A new era? Severan inscriptions in Africa / Gareth Sears -- The city as preferred written space: the case of Aquitania / Simon Esmonde Cleary -- The written city : political inscriptions from Roman Baetica / Louise Revell -- Afterword / Peter Keegan